INDONESIA HOME COUNTRY INDEGENIOUS KNOWLEDGE AND TRADISIONAL WISHDOM FOR GROWING SEASON OF LAND PADDY - Abd. Syakur, Sayani (AGROLAND: The Agricultural Sciences Journal, 2015)
The aim of this research is to determine growing season land paddy with use tradisionally climate prediction base on indegenious knowledge and tradisionalwishdom from society where they live on remote area. The data of growth and yield of land paddy was collected at Powelua Village, Donggala regency, Central Sulawesi Province, Indonesia. The method of this research use survey and interview in depth to farmer who planted land paddy. The result show that their knowledge to predict climate for growing season land paddy has to used both the climate data.